The exercise of constitutionality control by the Peruvian judges - Sequeiros Vargas, Iván (2020)
Judges have the authority and must not apply a statutory law contrary to the Constitution in order to contribute to preserve constitutional supremacy, as an example of the good governance and government development; notwithstanding, in over twenty seven years, the Judiciary, on very few occasions, has declared a statutory law not applicable, which proves the reluctance to exercise this authority. Constitutional control is a complex task and judges avoid it due to all different implications that could result from their decisions. Additionally, the assumption indicated by the Constitutional Court regarding «clear incompatibility» would probably be one of the reasons influencing limited control enforcement, because no regulation turns out to be clearly non constitutional or vice versa at the sight of a good assessor. It results in an uncertain, unfeasible, and subjective concept, which does not limit or serve as reference for a judge to perform the control conferred on him by the Constitution and the law